TRANFORMASI DARI STRUKTURAL POLITIK KE KULTURAL: DINAMIKA PENERAPAN SYARIAH ISLAM (BANK SYARIAH DAN JILBAB SEBAGAI STUDI KASUS DI INDONESIA) - Dwi Purwoko (Jurnal Ilmu dan Budaya, 2018)
Religious awareness in society is increasing. This can be seen from the increasingly widespread use of the veil in society, the emergence of awareness to save money in syraiah institutions, the rise of people uintuk go to the holy land of Mekakh both Umtoh and hajj, the number of pengajian, tabligh akbar and the emergence of Sufi urban mostly jamaahnya young Muslim well established and so on. Regardless of the symbolic or subtasni it seems that the dynamics of the application of syaraiah have appeared cultivally in the cultural line after the "failure" of structural political struggle of the previous era. Coupled with the emergence of a class of Muslims who have an awareness of the meaning of syraiah in his life. Tamp [aknya specially the emergence of my bank can not be separated from the great flow of awareness of the ummah to save money in the banking institution. The rise of banking syaraiah an interesting phenomenon to be studied. Initial forming process like what. Its development, the meaning of syarakah that blesses itself. Muslim society's perception on syariat bank and hope of existence of bank syraiah in the future. The method used in this research is qualitative with the emphasis on the interpretation of the data obtained through interviews with some informants who were made the key informants involved in the flow of syarah in banking. Also public figures and religions that memehi hakeket syaraiah which is considered important in the world perbasnkan Regulation about the development of Islamic banking Maupoun Jilabab seems to have given some legal certainty maupoun norm for the development of banks and veils are expected by the Muslim community who seek to invest in banks and cata dress which is considered self-Allah Almighty. Mass media in the form of electronic media and the preachers as a form of mass communication as an agent in disseminating Islamic banks and jilab has also mendinamisasi the development of Islamic banks and hijab homeland. All are reinforced by the MUI Fatwa which becomes a mandatory  appeal to the extent possible to secure the money of theMuslim community to the sharia bank or the manner of appointment which is considered as a bank that upholds the values of justice and is considered in accordance with the principles of syrariah.